2002
DOI: 10.1176/appi.ajp.159.6.909
|View full text |Cite
|
Sign up to set email alerts
|

Contact With Mental Health and Primary Care Providers Before Suicide: A Review of the Evidence

Abstract: Objective-This study examined rates of contact with primary care and mental health care professionals by individuals before they died by suicide.Method-The authors reviewed 40 studies for which there was information available on rates of health care contact and examined age and gender differences among the subjects.Results-Contact with primary care providers in the time leading up to suicide is common. While three of four suicide victims had contact with primary care providers within the year of suicide, appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
821
6
46

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,304 publications
(910 citation statements)
references
References 46 publications
37
821
6
46
Order By: Relevance
“…Other studies have indicated that on average, as many as 45.0% of persons who die by suicide had visited their primary care physician within 1 month of their death (28) and as many as 67.0% of persons who attempt suicide receive medical attention as a result of their attempt (29). Such findings suggest opportunities for suicide prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have indicated that on average, as many as 45.0% of persons who die by suicide had visited their primary care physician within 1 month of their death (28) and as many as 67.0% of persons who attempt suicide receive medical attention as a result of their attempt (29). Such findings suggest opportunities for suicide prevention.…”
Section: Discussionmentioning
confidence: 99%
“…A review of healthcare contact before suicide indicated that 64% of decedents made contact with healthcare providers within a month (30 days) of their suicide (Luoma et al, 2002). However, few studies examined factors that were associated with immediate or near-term risk.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 First, patients dying by suicide visit primary care physicians more than twice as often as mental health clinicians. 10 A review of studies analyzing this clinical scenario estimated 45% of those dying by suicide saw their primary care physician in the month before their death. 10 Only 20% saw a mental health professional 10 in the preceding month.…”
Section: Importance To Primary Carementioning
confidence: 99%
“…10 A review of studies analyzing this clinical scenario estimated 45% of those dying by suicide saw their primary care physician in the month before their death. 10 Only 20% saw a mental health professional 10 in the preceding month. Women and older patients are more likely to have sought care in the month before suicide 10 than men and younger patients.…”
Section: Importance To Primary Carementioning
confidence: 99%
See 1 more Smart Citation